Pengembangan Pengajaran Bahasa Inggris Komunitas Isco Melalui Integrasi Teknologi - Tandi Rerung, Kartika Sari; Junita, Junita (Universitas Negeri Makassar, 2025)
This research outlines a comprehensive five-phase approach based on the ADDIE instructional design framework to enhance English language teaching at ISCO learning centers. Needs analysis identified challenges such as traditional methods, limited digital tool integration, and varying tutor preparedness. In response, a comprehensive, technology-integrated English syllabus was developed, featuring monthly thematic units and a simplified ESA structure, accommodating both digital and offline tools. Pilot testing and training phases equipped tutors with skills in digital tool usage and modern pedagogical strategies. Initial tutor feedback was positive regarding clarity, structure, language, activity variety, and material practicality in low-resource settings. While digital infrastructure and scheduling constraints were identified, the project successfully developed a curriculum framework and trained tutors for more interactive and relevant English teaching, aligning with ISCO's needs and moral development goals.Keywords: English language teaching, syllabus design, digital based learning